The Highlands and Islands of Scotland in transition - Mose, Ingo; Jacuniak-Suda, Marta (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2016)
The Highlands and Islands of Scotland represent a dramatic mountain-seascape which for long has been regarded one of the "classicâ€ peripheries of Europe. This perception was mainly based on a rather homogenous picture of a residual problem area in terms of economic and socio-cultural disparities which did persist to considerable extent up until recently. However, as rural areas throughout Europe presently are undergoing significant processes of structural change, including economic, social, cultural and political adjustment in the context of globalization, a much more diverse picture of rural peripheries in Europe is emerging. As such the Highlands and Islands provide an outstanding example of recent restructuring not yet fully recognized outside Britain. This is particularly true for the Western Isles, a chain of islands on the western fringe of the country facing major challenges regarding economicÂ Â  performance and social well-being of its population. Against the background of an ecologically fragile mountain-seascape people of the islands find themselves increasingly involved in fundamental debate about appropriate ways of future development. As selected case studies show the idea of sustainability provides a conceptual frame that seems at the core of the present discourse. Several initiatives and projects reflect opportunities but also obstacles connected with the ongoing process of transition.